Enhanced adsorption of Cd(II) using a composite of poly(acrylamide-co-sodium acrylate) incorporated LDH@MoS24−. Issue 3 (28th January 2020) - Yang, Mei; Peng, Liang; Chen, Anwei; Zeng, Qingru; Shao, Jihai; Luo, Si; Gu, Jidong
ABSTRACT: The Mg/Al layered double hydroxide (Mg/Al-LDH) intercalated with the MoS 4 2 − (MoS4 -LDH) impregnated into poly(acrylamide-co-sodium acrylate) (PP) was synthesized as layered double hydroxides-PP (LDHS-PP), whose characterization, adsorption properties and mechanisms were investigated. The maximum adsorption capacity ( q m ) for Cd(II) was ∼2789.58 mg/g by 1% LDHS-PP, while it was ∼1893.09 mg/g by PP, which indicated that the MoS4 -LDH greatly improved the Cd(II) uptake for PP in aqueous solution. In strongly acidic conditions (∼pH 3.0), there was still a good removal efficiency of about 45.65% by the 1% LDHS-PP, while that of PP was almost zero. At pH 5.0 the removal efficiency increased to 85.17% by the 1% LDHS-PP. The sorption kinetics for the 1% LDHS-PP was described well by a pseudo-second-order kinetic model. X-ray photoelectron spectrometry (XPS) and elemental distribution maps further confirmed the presence of MoS4 -LDH in the PP and most of the Cd(II) chemisorption based on the Cd-S bonding. Due to its high removal efficiency and acid resistance, LDHS-PP is a promising in-situ fixation agent for the remediation of agricultural soil polluted with Cd(II) at low pH. GRAPHICAL ABSTRACT: